Where should governments invest? The impact of economic, political, social and technological factors on the formation of new firms - Martha Garcia-Murillo; Jorge Andres Velez-Ospina; Patricia Vargas-Leon (International Telecommunications Society (ITS), 2012)
The purpose of this paper is to identify the factors that affect the creation of new firms. We take into consideration economic, political, social and technological factors which should also help governments realize the areas that we found to have the greatest impact. The study relies on data from international organizations from which we construct an ordered probit statistical analysis. The results indicate that investments in both ICT and education enhance the probability of generating new business.
Keywords: 330; New business; ICTs; governance; income; credit; education; trade